Challenges of Educational Technology Implementation in Indonesia: Digital Gap Analysis, Teacher Readiness, and Infrastructure Strengthening Strategies - Ahmad Fahrurroziqin; Risqi Maulana Achmad; Nur Anim Jauhiriyah (ICO EDUSHA, 2025)
The implementation of educational technology in Indonesia is inevitable amidst the development of the digital era and the demands for improving the quality of education. However, its implementation still faces various complex challenges. This article aims to analyze the main challenges in the implementation of educational technology in Indonesia, with a focus on the digital divide, teacher readiness, and strategies for strengthening educational infrastructure. The research method used is library research, reviewing various scientific sources such as journals, books, and relevant policy reports. The results of the study indicate that the digital divide still exists significantly between urban and rural areas, both in terms of internet access, device availability, and students' digital literacy. Furthermore, teacher readiness to utilize learning technology remains relatively low, marked by limited technology-based pedagogical competencies and a lack of ongoing training. Furthermore, educational technology infrastructure is not evenly distributed and does not fully support effective digital learning. Therefore, strategies are needed to strengthen infrastructure through equitable internet access, increasing the capacity of educational human resources, and synergy between the government, educational institutions, and the private sector. The inclusive and sustainable implementation of educational technology is expected to improve the quality and equity of education in Indonesia.